Reducing the Salt Added to Takeaway Food: Within-Subjects Comparison of Salt Delivered by Five and 17 Holed Salt Shakers in Controlled Conditions. - Louis Goffe; Wendy Wrieden; Linda Penn; Frances Hillier-Brown; Amelia A Lake; Vera Araujo-Soares; Carolyn Summerbell; Martin White; Ashley J Adamson; Jean Adams (PLoS ONE)
Objectives To determine if the amount of salt delivered by standard salt shakers commonly used in English independent takeaways varies between those with five and 17 holes; and to determine if any differences are robust to variations in: the amount of salt in the shaker, the length of time spent shaking, and the person serving. Design Four laboratory experiments comparing the amount of salt delivered by shakers. Independent variables considered were: type of shaker used (five or 17 holes), amount of salt in the shaker before shaking commences (shaker full, half full or nearly empty), time spent shaking (3s, 5s or 10s), and individual serving. Setting Controlled, laboratory, conditions. Participants A quota-based convenience sample of 10 participants (five women) aged 18-59 years. Main outcome measures Amount of salt delivered by salt shakers. Results Across all trials, the 17 holed shaker delivered a mean (SD) of 7.86g (4.54) per trial, whilst the five holed shaker delivered 2.65g (1.22). The five holed shaker delivered a mean of 33.7% of the salt of the 17 holed shaker. There was a significant difference in salt delivered between the five and 17 holed salt shakers when time spent shaking, amount of salt in the shaker and participant were all kept constant (p<0.001). This difference was robust to variations in the starting weight of shakers, time spent shaking and participant shaking (ps</ = 0.001). Conclusions Five holed salt shakers have the potential to reduce the salt content of takeaway food, and particularly food from Fish & Chip shops, where these shakers are particularly used. Further research will be required to determine the effects of this intervention on customers' salt intake with takeaway food and on total dietary salt intake.